Diagnosis of plant morphology misconceptions using a two-tier diagnostic test - Aidha Rizki Rosiananda; Wisanti Wisanti; Siti Zubaidah (Biosfer: Jurnal Pendidikan Biologi, 2026)
Misconceptions are a problem in biology education because of the mismatch between individual knowledge and scientific concepts. Misconceptions need to be identified promptly to prevent them from hindering further knowledge construction. This study aims to identify misconceptions about plant morphology among 11th-grade high school students in Surabaya. The research design was a descriptive survey, with 114 11th-grade students from 9 high schools in Surabaya as participants. The research instrument was a plant morphology two-tier diagnostic test (PLANT-MOOD) consisting of 10 questions covering conceptual questions at the first level and reasons for answers at the second level. The research was carried out in two main stages, namely the test instrument development stage and the test implementation stage. PLANT-MOOD was highly valid (96.9%) as assessed by four botany experts and was declared 100% valid based on the MNSQ, ZSTD, and Pt Measure Corr criteria. PLANT-MOOD was also highly reliable with a Cronbach's alpha of 0.85. Data analysis used the Rasch option probability curve model and simple statistics expressed as percentages. The study found that students had a high level of misconceptions, namely 63% (17 misconceptions identified). The highest misconception was 77% regarding achene, known as strawberry seeds, and the lowest misconception was 38% regarding the concept of sweet potato tubers resulting from stem modification. The results of the misconception profile diagnosis provide educators with information for designing more effective learning strategies.